Knowledge, beliefs, and practices of people with Type 2 diabetes toward self-management and diabetic foot - Naguib, Hani; Raman, Shiju; Pinto, Avinash; Al Mehrezi, Aisha; Al Hinaii, Aziza (Journal of Diabetes and Endocrine Practice, 2021)
Introduction: Diabetic foot syndrome is one of the most common and devastating preventable complications of diabetes mellitus. Knowledge and awareness about the disease can have a positive influence on attitude and practices of patients. Objectives: We aimed to evaluate the knowledge, beliefs, and practices (KBPs) regarding diabetes and diabetic foot syndrome among Omani type 2 diabetic patients. Patients and Methods: We studied 150 participants from the diabetes clinic, Bausher Polyclinic, Muscat. A questionnaire was used to determine KBPs around diabetic foot care. Results: There were 90 females and 60 males, 67.9% were older than 50 years, 42.7% were illiterate, and 72% of them were not working or retired. Only 38% checked their feet regularly; 5.6% had diabetic foot syndrome. Over half of the respondents (55.3%) did not know the causes of diabetic foot syndrome and half of the respondents did not know symptoms of the same. Just over one-third (37.3%) thought that their doctor alone was responsible for foot examination. Only 32.7% thought that they should examine their own feet. The majority believed that walking barefoot and diabetic foot syndrome are “big” problems (84% and 80%, respectively). More than three-quarters (78%) reported checking water temperature before use, 38.7% use warm water for washing feet, and 39.3% reported drying their feet after washing. Only 38% check their feet regularly. Finally, only one-third confirmed checking their blood sugar regularly. Conclusions: The KBP triad must be interconnected in order to achieve successful preventive foot care.
Keywords: Attitude; diabetic foot; knowledge; practices